Iowa Birdline update, August 24, 1992 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1992)
Email for the Iowa Birdline update for August 24, 1992. Highlights of the update include sightings of Least Bittern, Ruddy Turnstone, American Avocet, Willet and a Black-bellied Plover. Also included are handwritten notes for the next week's update with sightings of two Piping Plovers at the Sandpiper Recreation area and fourteen additional species of shorebirds at Red Rock Reservoir. Epson - sheet feed/flatbed